Cover crops for managing weeds, soil chemical fertility and nutritional status of organically grown orange orchard in Sicily - Rosario Paolo Mauro; Umberto Anastasi; Sara Lombardo; Gaetano Pandino; Roberto Pesce; Restuccia Alessia; Giovanni Mauromicale (Italian Journal of Agronomy)
Cover crops can offer significant advantages in the agronomic management of citrus orchards in Mediterranean environments. Therefore, a three-year research was conducted in eastern Sicily aimed at studying the effects of four cover crop sequences (Sinapis arvensis-Trigonella foenum-graecum-T. foenum-graecum; Medicago scutellata-Avena sativa-Lolium perenne; Vicia faba minor-A. sativa-A. sativa; A. sativa-V. faba. minor-L. perenne) on weeds, major soil chemical properties and nutritional status of an organically grown orange orchard. The results highlighted that, among the studied cover crop sequences, Vicia faba-Avena-Avena was the most beneficial for weeds control within the orchard (92%, of cover crop cover, and 586 and 89 g DW m–2 of cover crop aboveground biomass and weeds aboveground biomass, respectively). Overall, the chemical fertility of the soil was positively influenced. In particular, it was observed an increase of the content of total nitrogen and available phosphorus in the soil by both Sinapis-Trigonella-Trigonella (0.75 g kg–1 and 59.0 mg kg–1, respectively) and Vicia faba-Avena-Avena (0.70 g kg–1 and 56.0 mg kg–1, respectively) cover crop sequences. Medicago-Avena-Lolium sequence seemed to be the most useful to ensure a better nutritional status of the orange orchard.